Mitochondrial-Targeted Ratiometric Fluorescent Probe to Monitor ClO− Induced by Ferroptosis in Living Cells - Feng, Beidou; Wang, Kui; Wang, Zhe; Niu, Huiyu; Wang, Ge; Chen, Yuehua; Zhang, Hua (Frontiers in Chemistry, 2022)
Ferroptosis is a type of iron-dependent programmed cell death. Once such kind of death occurs, an individual cell would undergo a series of changes related to reactive oxygen species (ROS) in mitochondria. A mitochondrial-targeted ratiometric fluorescent probe (MBI-OMe) was developed to specifically detect ferroptosis-induced ClO−, whose recognition group is p-methoxyphenol, and the mitochondrial-targeted group is benzimidazole. The fluorescence of MBI-OMe was first quenched by 30 μM of Fe3+, and then MBI-OMe appeared as a ratiometric signal at 477 nm and 392 nm in response to ferroptosis-induced ClO− in living cells. MBI-OMe was successfully used to evaluate changes in ClO− induced by ferroptosis.